Fiber optic nickel ion sensor based on direct ligand immobilization - Raghunandhan, Ravikumar (2019)
An inline intermodal no core fiber (NCF) sensor based on direct ligand immobilization for detection of nickel ions (Ni2+) is proposed. Covalently immobilized nickel specific ligand, Meso-Tetra(4-carboxyphenyl)porphine, on the NCF surface serves as adsorption site for Ni2+ and can induce ambient refractive index (RI) change around the NCF on occurrence of binding events. The change in RI results in spectrum wavelength shifts, which was measured for continuous monitoring of Ni2+ concentration. The proposed sensor was observed to exhibit a sensitivity of 121.03 nm/mM towards Ni2+ ions.